Karateristik Pulau Masela Perspektif Antropologi Pulau Kecil - Wakim, Mezak (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2020)
This paper describes Masela Island through an anthropological approach, highlighting its remarkable cultural wealth. As a small island, it plays a significant role in developing strategic national issues concerning Indonesia's outermost islands. The paper examines the perspective of utilizing small islands by focusing on Masela Island, one of the small islands in the Southwest Maluku Regency, Maluku Province, through the lens of minor island anthropology. The management model of small islands is now a social reality. Masela is a small island that boasts many advantages in cultural development but still needs to be noticed due to geographical constraints. However, the potential for artistic development on Masela Island is highly promising.Masela Island is also considered a small island bordering Australia, making it vulnerable to various social upheavals that could affect the local culture in Maluku. This paper aims to reveal the potential of Masela Island as a small island in Maluku from an anthropological perspective, focusing on the cultural advantages of small islands. The method is descriptive with a qualitative approach, employing data collection techniques such as interviews, observations, and literature reviews. The findings of this paper show that Masela Island, as a small island with significant cultural potential, complements the cultural heritage of the communities on the small islands of Southwest Maluku.